GEA completes Hilge acquisition. Issue 10 (October 2015) - Unknown
Abstract : GEA has closed the acquisition of hygienic pump manufacturer Hilge from Grundfos, following approval by the relevant antitrust authorities (see Pump Industry Analyst, July 2015).